Evaluation of pai-1 polymorphisms in central and peripheral thromboembolies - Arıcı Düz, Özge; Olmuşçelik, Oktay; Gemici, Aliihsan; Saatçi Sancaktepe, Özlem (Ondokuz Mayıs Üniversitesi, 2021)
Thromboembolism is a clinical finding that occurs due to thrombus; formed in the vascular system and has various etiological factors. It can be classified as central and peripheral thromboembolism. Our objective in this study is to explore genetic risk factors in central and peripheral thromboembolism and reveal the differences. 342 thromboembolism patients were retrospectively included to the study between January 2016 and December 2019. Demographic characteristics, risk factors for thromboembolism and genetic mutations in central and peripheral thromboembolism groups were overviewed. The genetic mutations evaluated in patients were Factor V Leiden G1691A, Factor V HR1299R, Factor II (Prothrombin) G20210A, MTHFR (Methylenetetrahydrofolate reductase) C677T, MTHFR A1298C, PAI 4G/5G. Within the scope of the study, genetic analyzes of 106 patients were reached and included in the study. Seventy-two central thromboembolism (69.8%), 34 (31.2%) peripheral thromboembolisms were detected. Sixty-three of the central thromboembolisms were from arterial and nine were from venous origin. There was no significant difference between age, gender and risk factors of central thromboembolism and peripheral thromboembolism patients (p0.05), but smoking was more common in central thromboembolism patients (p: 0.041). 4G/5G polymorphism was observed more frequently in patients with central thromboembolism (p: 0.039). Thromboembolism is a multifactorial disease, PAI-1 4G/5G polymorphism is a medium risk factor for thromboembolism. We conclude that PAI-1 4G/5G polymorphism is more frequent in central thromboembolism than peripheral thromboembolism and its evaluation can give more information about the thromboembolic risk analyze.
Keywords: Stroke; Pai; Thromboembolism; Mutations